PENGARUH MEDIA MAPTILER TERHADAP KREATIVITAS BERDASARKAN MOTIVASI BELAJAR GEOGRAFI MATERI PETA KELAS X. E1 DI SMAN 2 BATANG ANAI - Putri Andini; Bayu Wijayanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Maptiler digital learning media on student learning creativity in terms of geography learning motivation on map material in class X.E1 SMAN 2 Batang Anai. The background of this research is based on the low creativity and motivation of students in learning geography due to the dominance of monotonous conventional methods and the lack of utilisation of technology-based media. The research method used was quasi experimental design with non-equivalent control group design. The research sample consisted of two classes, namely the experimental class (using Maptiler media) and the control class (using conventional media), each totalling 30 students. The instruments used included pretest and posttest tests, learning motivation questionnaires, and assignments to measure student creativity. n conclusion, Maptiler media is effective in increasing geography learning creativity, especially for students who have high learning motivation. This research recommends the utilisation of interactive digital media as an innovative strategy in geography learning to create interesting, meaningful and creative learning